Aedes aegypti Toll pathway is induced through dsRNA sensing in endosomes. (September 2021) - Angleró-Rodríguez, Yesseinia I.; Tikhe, Chinmay V.; Kang, Seokyoung; Dimopoulos, George
Abstract: Mosquito anti-pathogen immune responses, including those controlling infection with arboviruses are regulated by multiple signal transduction pathways. While the Toll pathway is critical in the defense against arboviruses such as dengue and Zika viruses, the factors and mechanisms involved in virus recognition leading to the activation of the Toll pathway are not fully understood. In this study we evaluated the role of virus-produced double-stranded RNA (dsRNA) intermediates in mosquito immune activation by utilizing the synthetic dsRNA analog polyinosinic-polycytidylic acid (poly I:C). Poly I:C treatment of Aedes aegypti mosquitoes and Aag2 cells reduced DENV infection. Transcriptomic analyses of Aag2 cell responses to poly I:C indicated putative activation of the Toll pathway. We found that poly I:C is translocated to the endosomal compartment of Aag2 cells, and that the A. aegypti Toll 6 receptor is a putative dsRNA recognition receptor. This study elucidates the role of dsRNAs in the immune activation of non-RNAi pathways in mosquitoes. Highlights: Exposure of  Aedes aegypti  to polyinosinic:polycytidylic acid (poly I:C), a dsRNA analog, reduces dengue virus infection. Poly I:C induces Toll pathway-associated genes in Aag2 cells. Aedes aegypti Toll-like receptor 6 is a putative dsRNA recognition receptor.